Monitoring ultra high-voltage transmission tower deformation and corridor subsidence using China C-band Synthetic Aperture Radar and Sentinel-1 data - Yunlong Liu; Yujun Guo; Sijie Ma; Zhi Yang; Chaomin Chen; Guangning Wu; Wei Liu; Weijia Ren; Xiaoru Sang; Tao Li (Geocarto International)
Monitoring the ultra-high-voltage (UHV) transmission towers’ deformation is vital for the safety evaluation, especially in China, a global leader in UHV technology. This study examined Chongqing’s 500 kV transmission corridor using high-resolution C-band SAR data from Fucheng-1 and Sentinel-1A (S1A). Long-term S1A data revealed significant subsidence near an airport, while short-term Fucheng-1 data indicated corridor stability over the past two months. Four corner reflectors ensured precise geolocation calibration of Fucheng-1 imagery by mitigating random offsets. Differential interferograms from both ascending and descending Fucheng-1 data showed phase changes in the towers. LiDAR data was used to simulate tower elevation ambiguities, which were subtracted from the interferograms, revealing deformation phases. This study is the first to detect thermal expansion and stress-induced deformations of towers under varying temperatures. The results demonstrate the potential for enhancing the safety and reliability of China’s extensive UHV power network through advanced C -Band SAR monitoring technologies.